2010
DOI: 10.1510/icvts.2009.223040
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular graft deployment in the false lumen of type B dissection

Abstract: TEVAR for complicated type B dissection should be carried out according to a precise and stepwise protocol in institutions familiar with all the different options of conversion to open repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…Because the stent graft has to be advanced through segments with decreased wall strength, aortic rupture may be caused during the passage or the stent may be released in the false lumen. 1 To minimize these risks, interventional techniques using an antegrade approach via the subclavian artery or the use of a hybrid procedure with open implantation of an aortic stent before placement of the arch prosthesis have recently been described. [2][3][4] We developed a new and safe technique of antegrade stent graft placement via the already implanted prosthesis either after resternotomy or during the original procedure.…”
mentioning
confidence: 99%
“…Because the stent graft has to be advanced through segments with decreased wall strength, aortic rupture may be caused during the passage or the stent may be released in the false lumen. 1 To minimize these risks, interventional techniques using an antegrade approach via the subclavian artery or the use of a hybrid procedure with open implantation of an aortic stent before placement of the arch prosthesis have recently been described. [2][3][4] We developed a new and safe technique of antegrade stent graft placement via the already implanted prosthesis either after resternotomy or during the original procedure.…”
mentioning
confidence: 99%
“…There are a few reports of this kind of procedure. [3][4][5] As described in previous reports, surgical removal of the endoprosthesis is feasible but challenging. 5,6 A hybrid operation to maintain blood supply of the visceral arteries would be necessary before the interventional treatment but potentially traumatic.…”
Section: Discussionmentioning
confidence: 91%
“…However, a dissected and weakened vessel wall may rupture earlier after the stent graft has been unintentionally deployed into the false lumen. Previous reports of endograft deployment into the false lumen were described by Follisa and colleagues 3 and Zhang and colleagues. 4 In both of these studies, the guidewire was placed into the false lumen of the thoracic aorta arch during an attempt of TEVAR, similar to this case.…”
Section: Discussionmentioning
confidence: 99%
“…These complications are often repaired with a hybrid technique [4,7]. In this case, we demonstrated that the unusual complication of device misplacement into the false lumen of an aortic dissection can also be salvaged with a modified FET procedure [5,6].…”
Section: Commentmentioning
confidence: 84%
“…Compared with open operations in a meta-analysis, TEVAR had a decreased risk of several common major complications [2]. Proximal aortic complications unique to TEVAR include type 1 endoleaks, device migration, retrograde dissection, and rarely malpositioning in the false lumen [3][4][5][6]. These complications are often repaired with a hybrid technique [4,7].…”
Section: Commentmentioning
confidence: 99%